Oceanic Surveillance and Navigation Analysis, FY 71. - Hershkowitz,Ronald M. (1971)
The report summarizes the oceanic surveillance and navigation analysis performed at Transportation Systems Center under PPA FA-04 for FY 71. Three major efforts are reviewed and discussed herein: summary of the North Atlantic Systems Planning Group collision risk model; a study of the impact of inertial navigation on air safety; an investigation of the modeling techniques required to assess the effect of air traffic control satellite surveillance on separation standards in the North Atlantic region. (Author)